Traditional Beliefs as an Ecotheological Force for Sustainability: Reinterpreting Mori Keraéng Amid the Climate Crisis - Sefrianus Juhani; Hendrikus Maku; Ambros Leonangung Edu; Vinsensius Adi Gunawan (Jurnal Studi Agama dan Masyarakat, 2025)
The escalating climate crisis increasingly challenges theology to engage with ecological issues through contextual and inclusive approaches. While dominant eco-theological discourse often reflects Western paradigms, local cosmologies that embody ecological wisdom remain underrepresented. The study aimed to examine traditional beliefs as an eco-theological force for sustainability by reinterpreting Mori Keraéng, a Divine figure in Manggarai cosmology, through dialogue with Catholic eco-theology. The research employed a qualitative ethnographic method, using in-depth interviews and participant observation in historically and culturally significant villages in Manggarai and East Manggarai, involving traditional leaders, community heads, and local residents. The findings reveal that traditional practices such as ritual offerings, communal land management, and ecological taboos embody a living ecological ethic that restrains exploitation, fosters balance, and strengthens resilience against environmental degradation. These practices demonstrate that traditional spirituality functions not as a relic of the past, but as an active and transformative resource for sustaining life. The study affirms that local cosmologies, when theologically reinterpreted, can enrich Catholic ecological theology, contribute to global eco-theological discourse, and inspire sustainable practices to rebuild human-nature relations in the Anthropocene era.